Cognitive Functioning in Young Children with Type 1 Diabetes. (11th February 2014) - Cato, M. Allison; Mauras, Nelly; Ambrosino, Jodie; Bondurant, Aiden; Conrad, Amy L.; Kollman, Craig; Cheng, Peiyao; Beck, Roy W.; Ruedy, Katrina J.; Aye, Tandy; Reiss, Allan L.; White, Neil H.; et al.
Abstract: The aim of this study was to assess cognitive functioning in children with type 1 diabetes (T1D) and examine whether glycemic history influences cognitive function. Neuropsychological evaluation of 216 children (healthy controls, n = 72; T1D, n = 144) ages 4–10 years across five DirecNet sites. Cognitive domains included IQ, Executive Functions, Learning and Memory, and Processing Speed. Behavioral, mood, parental IQ data, and T1D glycemic history since diagnosis were collected. The cohorts did not differ in age, gender or parent IQ. Median T1D duration was 2.5 years and average onset age was 4 years. After covarying age, gender, and parental IQ, the IQ and the Executive Functions domain scores trended lower (both p = .02, not statistically significant adjusting for multiple comparisons) with T1D relative to controls. Children with T1D were rated by parents as having more depressive and somatic symptoms ( p < .001). Learning and memory ( p = .46) and processing speed ( p = .25) were similar. Trends in the data supported that the degree of hyperglycemia was associated with Executive Functions, and to a lesser extent, Child IQ and Learning and Memory. Differences in cognition are subtle in young children with T1D within 2 years of onset. Longitudinal evaluations will help determine whether these findings change or become more pronounced with time. ( JINS, 2014, 20, 238–247)